Analisis Strategi Promosi Wisata Untuk Meningkatkan Kunjungan Wisatawan Puncak Mas Sukadanaham Bandar Lampung - Afifa, Nur; Defrizal, Defrizal (CV. Lafadz Jaya, 2022)
The purpose of this research is to find out how the strategy and development of promotion during the COVID-19 pandemic at Puncak Mas Sukadanaham Tourism Destinations, Bandar Lampung. This thesis explains about observing, identifying, analyzing, evaluating, treating and describing how promotion strategies and promotion development are at the peak tourist destinations of Massukadanaham Bandar Lampung. This type of research is descriptive qualitative by conducting direct interviews with informants and data obtained exclusively in the field. Methods that can be used for data collection in this study are observation and documentation. So that they get the following results: 1) Puncakmas tourist destinations in choosing their target market do not make it specifically in identifying visitors who are the target market. 2) Puncakmas in conveying message information that has meaning in it in describing/telling the beauty of tourism objects and what attractions they have. 3) Media selection is in the form of word-of-mouth recommendations and indirect communication. The promotion development strategy is only carried out personally (word of mouth) and non-personally (print media, Instagram social media, and electronic media).